2019
DOI: 10.3390/ma12111750
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Axial Buckling of Laminated Composite Plates Including Cutout and Additional Mass

Abstract: In the presented paper, a study of bi-axial buckling of the laminated composite plate with mass variation through the cutout and additional mass is carried out using the improved shear deformation theory (ISDT). The ISDT mathematical model employs a cubic variation of thickness co-ordinates in the displacement field. A realistic parabolic distribution of transverse shear strains through the plate thickness is assumed and the use of shear correction factor is avoided. A C° finite element formulation of the math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Another example of FOSD was presented by Nguyen et al in 2019 [ 27 ] for advanced composite plates such as functionally graded plates, where no shear correction factor was used. In the literature, also the alternatives to FOSD may be found, for instance in the work of Anish et al [ 28 ], the so-called improved shear deformation theory was presented, in which a cubic variation of the thickness coordinate in the displacement field is employed.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of FOSD was presented by Nguyen et al in 2019 [ 27 ] for advanced composite plates such as functionally graded plates, where no shear correction factor was used. In the literature, also the alternatives to FOSD may be found, for instance in the work of Anish et al [ 28 ], the so-called improved shear deformation theory was presented, in which a cubic variation of the thickness coordinate in the displacement field is employed.…”
Section: Introductionmentioning
confidence: 99%
“…The study concludes that shear deformation laminate theories predict composite laminates behaviour accurately, while classical laminate theory overpredicts buckling loads. Anish et al [68] carried out a study with the use of improved shear deformation (ISDT) and C0 finite element formulations on a uni-axial and bi-axial buckling of the laminated composite plate with mass changes through cutout and an additional mass. The novel results are achieved by varying geometry, loading, boundary conditions and ply orientation.…”
Section: Static Free Vibration and Buckling Analysis Of Composite Pamentioning
confidence: 99%
“…Using first-order shear deformation theory (FSDT), Chaudhuri et al [ 11 ] studied five-mode shape analysis of hyper shell with cut-out and concluded that free vibration mainly depends upon boundary conditions rather than other parameters. With improved shear deformation theory (ISDT), Anish et al [ 12 ] analyzed bi-axial buckling of a laminated composite plate with cut-out and additional mass. By modelling uncertain material properties of FGPs with a multiple-imprecise-random-field model, Minh et al [ 13 ] performed a hybrid uncertainty analysis of FGPs.…”
Section: Introductionmentioning
confidence: 99%